Enhanced dust emissivity power-law index along the western H α filament of NGC 1569. Issue 3 (29th March 2018) - Suzuki, T; Kaneda, H; Onaka, T; Yamagishi, M; Ishihara, D; Kokusho, T; Tsuchikawa, T
Abstract : We used a data set from AKARI and Herschel images at wavelengths from 7 to 500 $μ$ m to catch the evidence of dust processing in galactic winds in NGC 1569. Images show a diffuse infrared (IR) emission extending from the galactic disc into the halo region. The most prominent filamentary structure seen in the diffuse IR emission is spatially in good agreement with the western H α filament (western arm). The spatial distribution of the F 350 / F 500 map shows high values in regions around the super-star clusters (SSCs) and towards the western arm, which are not found in the F 250 / F 350 map. The colour–colour diagram of F 250 / F 350 – F 350 / F 500 indicates high values of the emissivity power-law index (βc ) of the cold dust component in those regions. From a spectral decomposition analysis on a pixel-by-pixel basis, a βc map shows values ranging from ∼1 to ∼2 over the whole galaxy. In particular, high βc values of ∼2 are observed only in the regions indicated by the colour–colour diagram. Since the average cold dust temperature in NGC 1569 is ∼30 K, βc < 2.0 in the far-IR and sub-mm region theoretically suggests emission from amorphous grains, while βc = 2.0 suggests that from crystal grains. Given that the enhanced βc regions are spatially confined by the H i ridge that is considered to be a birthplace of the SSCs, the spatial coincidences may indicate that dust grains around the SSCs are grains of relatively high crystallinity injected by massive stars originating from starburst activities and that those grains are blown away along the H i ridge and thus the western arm.